Characteristics of Primary Glaucoma in Glaucoma Clinic of Dr. Mohammad Hoesin General Hospital, Palembang - Prima Maya Sari; Rizka Yunanda (Sriwijaya Journal of Ophthalmology, 2022)
Introduction: Glaucoma is the second leading cause of blindness for over 70 million people worldwide. Bilateral blindness occurs with an estimated 10%. In Indonesia, the prevalence of glaucoma is 0,46%. That means that 4 to 5 out of 1.000 people suffer from glaucoma. Considering glaucoma as the second cause of blindness after cataracts in the world and its irreversible nature, this study was conducted to determine the characteristics of patients with primary glaucoma in the Glaucoma Clinic, Dr. Mohammad Hoesin General Hospital in 2021 based on age, gender, diagnosis, and intraocular pressure. Methods: This research is a descriptive retrospective study using secondary data through the medical record of patients in the Glaucoma Clinic, Dr. Mohammad Hoesin General Hospital Palembang from January to December 2021. The sample of this study was 20 people, and there were 40 eyes diagnosed with primary glaucoma. Results: The number of Primary Glaucoma patients was more in female patients, namely 11 patients (55,0%) with age varies at ≤ 50 years of age (45,0%), namely 51-60 patients (35,0%) and aged ≥ 61 years as many as 4 patients (25%), with an age range from 40 years to 70 years. Most patients were POAG (85%), with the highest eye pressure was 38,8mmHg, and 43,4 mmHg in PACG. Conclusion: There were 20 cases of primary glaucoma at the Glaucoma Clinic of Dr. Mohammad Hoesin General Hospital Palembang in 2021 with 40 affected eyes. Most patients were female, with most age group <50 years, and the most common type of glaucoma was open-angle.